Identification of Morphology and Molecular PCR-RAPD Bactrocera spp. in the Location of Red Guava Crops, Deli Serdang District - Sari, Putri Mustika; Lisa, Oviana; Lisdayani, Lisdayani (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Various fruit flies are in Indonesia, but only a few species of fruit flies have been found at the red guava plant in Deli Serdang District. Knowing the species of fruit flies are needed to do the proper control. In addition to morphological identification, it is necessary to carry out molecular characterization to obtain accurate results in characterizing species differences. This study aims to identify the fruit fly based on morphology and molecularly PCR-RAPD for mapping the genetic closeness of the relationship between individual fruit flies. Bactrocera morphologically identified at LIPI, namely B. carambolae, B. papayae, B. caudata, B. albistrigata, B. umbrosa, B. curcubitae, B. tau, and B. kinabalu. For molecular identification PCR-RAPD, shows the dendrogram results from the Neighbor-Joining analysis based on RAPD markers of DNA band characters showing the genetic proximity of eight species divided into three groups of Bactrocera based on their location. The closeness of genetic relationships between individuals was analyzed using Pairwise Distance Calculation which describes the genetic distance between species. The results of Pairwise Distance Calculation ranged from 0.13-0.42. By knowing what species there fruit flies are in red guava plantations in the Deli Serdang district, it can make it easier for farmers to monitor and control fruit flies in red guava plantations.